UPAYA DESA API-API DALAM MENJADI DESA TERBAIK SE KABUPATEN BENGKALIS TAHUN 2012 - Iskandarsyah "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study examines the efforts of the village in the Api-Api be the best village of Se Bengkalis in 2012 and are the focus of this study is what the efforts made Village Api-Api to be the best village of Se Kebupaten Bengkalis. In this research using descriptive qualitative method, is the effort to collect, collate and interpret existing data and then analyze the data, examine, describe and examine more clearly from a variety of factors related to the conditions, situations and phenomena were investigated. This research method could certainly describe the journey of an idea or thought involved in matters that are limited in this study. This study used an interview with the informant as an object in this study. The type of data used in this study are primary data and secondary data. The results showed in the efforts undertaken by the Village Api-Api, there are some attempts by Api-Api village as in the health sector efforts made increase knowledge and awareness of village communities on health, immunization, education efforts made to provide scholarships to needy households, facilitate the maintenance of poor letter, in the field of institutional efforts made to provide facilities infrastructure, in the areas of village government efforts made to foster employee discipline, education and training, in the field of community economic assistance efforts of the agricultural infrastructure, fostering , direct and control of agricultural products with the help of the Department of agriculture. Keywords: effort, village administration, policy, coordination.